Characterization of DNA Repair Foci in Root Cells of Arabidopsis in Response to DNA Damage - Hirakawa, Takeshi; Matsunaga, Sachihiro (Frontiers in Plant Science, 2019)
As a sessile organism, plants are constantly challenged by diverse environmental stresses that threaten genome integrity by way of induction of DNA damage. In plants, each tissue is composed of differentiated cell types and the response to DNA damage differs among each cell type. However, limited information is available on the DNA repair activity of different cell types in response to DNA damage in plants. A chromatin remodeling factor RAD54, which plays an important role in alteration of chromatin structure during homologous recombination, specifically accumulates at damaged sites, forming DNA repair foci (termed RAD54 foci) in nuclei after γ-irradiation. In this study, we performed a time-course analysis of the appearance of RAD54 foci in root cells of Arabidopsis after γ-irradiation to characterize the nuclear dynamics in each cell type. A short time after γ-irradiation, no significant difference in detection frequency of RAD54 foci was observed among epidermal, cortical, and endodermal cells in the meristematic zone of roots. Although the majority of cells lacked RAD54 foci for a long time after γ-irradiation, large RAD54 foci were detected in some cells of the root. Interestingly, RAD54 foci in these cells were localized to the nuclear periphery with high frequency. These observations suggest that the nuclear envelope plays a role in the maintenance of genome stability in response to DNA damage in Arabidopsis roots.